2018
DOI: 10.1111/gwao.12228
|View full text |Cite
|
Sign up to set email alerts
|

Unions and social media: Prospects for gender inclusion

Abstract: The emergence of web 2.0 technologies led to optimistic predictions that social media (SM) might alter traditional gendered patterns of member participation in trade unions. Greene, Hogan, and Grieco and others suggested that the forms of communication and engagement these technologies offered to unions and their members had the potential to foster gender inclusion and contribute to union diversity, arguably central to effective representation. This article reports on a survey of union members’ experiences wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…The work of Panagiotopoulos () and Panagiotopoulos and Barnett () offers useful insights into the views of union members and officials towards union adoption of social media platforms, suggesting that younger people are more likely to engage with unions on social media and could be recruited online (Panagiotopoulos, : 186). Thornwaite et al () surveyed union members about their experiences with social media to investigate the impact of gender on social media use, and found that women were just as likely, if not more likely, to engage with their union on social media. In their study of online freelancers, Wood et al () found that social media groups played a central role in communication where traditional unions are absent, highlighting the importance of Internet‐based communities for workers.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The work of Panagiotopoulos () and Panagiotopoulos and Barnett () offers useful insights into the views of union members and officials towards union adoption of social media platforms, suggesting that younger people are more likely to engage with unions on social media and could be recruited online (Panagiotopoulos, : 186). Thornwaite et al () surveyed union members about their experiences with social media to investigate the impact of gender on social media use, and found that women were just as likely, if not more likely, to engage with their union on social media. In their study of online freelancers, Wood et al () found that social media groups played a central role in communication where traditional unions are absent, highlighting the importance of Internet‐based communities for workers.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…First, Greene and Kirton (2003) identify the potential to engage online with ‘atypical’ members. Kerr and Waddington (2013) offer mixed evidence that this is actually happening with women and part‐time workers while Thornthwaite et al ., (2018) found that men and women were engaging with union social media accounts to the same degree and for the same purposes. From the perspective of members, digital skills and familiarity with preferred channels might affect their willingness to interact on social media even irrespective of offline engagement (Panagiotopoulos, 2012).…”
Section: Conceptualising Unions’ Digital Audiencesmentioning
confidence: 97%
“…Trade unions, particularly male-dominated unions, have generally been slow to recognise women's lagging under-representation and under-participation (Thornthwaite et al, 2018).…”
Section: Union Responses To Women's Under-representation and Under-participationmentioning
confidence: 99%